3D printed TPMS structural PLA/GO scaffold: Process parameter optimization, porous structure, mechanical and biological properties. (June 2023) - Guo, Wang; Yang, Yanjuan; Liu, Chao; Bu, Wenlang; Guo, Feng; Li, Jiaqi; Wang, Enyu; Peng, Ziying; Mai, Huaming; You, Hui; Long, Yu
Abstract: Bone scaffolds should have good biocompatibility and mechanical and biological properties, which are primarily by the material design, porous structure, and preparation process. In this study, we proposed polylactic acid (PLA) as the base material, graphene oxide (GO) as an enhancing filler, triply periodic minimal surface (TPMS) as a porous structure, and fused deposition modeling (FDM) 3D printing as a preparation technology to develop a TPMS structural PLA/GO scaffold and evaluate their porous structures, mechanical properties, and biological properties towards bone tissue engineering. Firstly, the influence of the FDM 3D printing process parameters on the forming quality and mechanical properties of PLA was studied by orthogonal experimental design, based on which the process parameters were optimized. Then, GO was composited with PLA, and PLA/GO nanocomposites were prepared by FDM. The mechanical tests showed that GO can effectively improve the tensile and compression strength of PLA; only by adding 0.1% GO the tensile and compression modulus was increased by 35.6% and 35.8%, respectively. Then, TPMS structural (Schwarz-P, Gyroid) scaffold models were designed and TPMS structural PLA/0.1%GO nanocomposite scaffolds were prepared by FDM. The compression test showed that the TPMS structural scaffolds had higher compression strength than the Grid structure; This was owing to the fact that the continuous curved structure of TMPS alleviated stress concentration and had a more uniform stress bearing. Moreover, cell culture indicated bone marrow stromal cells (BMSCs) showed better adhesion, proliferation, and osteogenic differentiation behaviors on the TPMS structural scaffolds as the continuous surface structure of TPMS had better connectivity and larger specific surface area. These results suggest that the TPMS structural PLA/GO scaffold has potential application in bone repair. This article suggests the feasibility of co-designing the material, structure, and technology for achieving the good comprehensive performance of polymer bone scaffolds.